2016
DOI: 10.1007/978-3-319-33111-9_71
|View full text |Cite
|
Sign up to set email alerts
|

PLM-MES Integration: A Case-Study in Automotive Manufacturing

Abstract: Nowadays, the development of high-quality, highly-innovative products is mandatory to satisfy the market requests. To support this process, the deployment of IT tools, such as Product Lifecycle Management (PLM) and Manufacturing Execution Systems (MES), is necessary. However, the efficacy of such instruments can be increased if they are able to exchange information with each other. Such integration provides the designers with a feedback from the shop-floor: this allows to improve the quality of the product and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The Data-to-Information Conversion Level allows the access to information of the large volume of data collected, for example, knowledge about the useful life of the machines and their performance (Lee et al, 2015;Qin et al, 2016). In this case, the sensors that monitor temperature, vibrations, noise or wear are crucial (D'Antonio et al, 2015;Vachálek et al, 2017).…”
Section: Pilot Project Developmentmentioning
confidence: 99%
“…The Data-to-Information Conversion Level allows the access to information of the large volume of data collected, for example, knowledge about the useful life of the machines and their performance (Lee et al, 2015;Qin et al, 2016). In this case, the sensors that monitor temperature, vibrations, noise or wear are crucial (D'Antonio et al, 2015;Vachálek et al, 2017).…”
Section: Pilot Project Developmentmentioning
confidence: 99%
“…Another interesting article is a PLM-MES integration proposal for a collaborative design of a spur gear production [25]: an appealing case-study because the accuracy required for this product is very high with a consequential very high unitary cost. The same authors elaborated a PLM-MES integration applied on the automotive manufacturing [26], by focusing on how the real-time monitoring activity of the MES can improve the PLM. A survey submitted to a set of Italian companies to measure their digital maturity and their proneness in implementing further PLM and MES solutions and their integration was also presented [27].…”
Section: Related Workmentioning
confidence: 99%
“…In previous work, D'Antonio et al [16] identified the benefits resulting from the integration between PLM and MES through a case-study in the manufacturing of aeronautics components. In [17], a case-study in the field of automotive has been analyzed. In both the two works, the main benefit deriving from the integration between the two systems could be the reduction of errors in information management and the improved reactivity in taking decisions.…”
Section: Integration Between Plm and Mesmentioning
confidence: 99%